Penerapan Project Penguatan Profil Pelajar Pancasila Terhadap Karakter Siswa - Farma, Febriansyah (Yayasan Sembilan Pemuda Indonesia, 2024)
This study aims to analyze the implementation of the Pancasila Student Profile Strengthening Project (P5) as an effort to strengthen student character including design; management; assessment processing and reporting of results; evaluation and follow-up. This study uses a descriptive qualitative method at State Elementary School 27, Palembang City in 2024. Data collection methods include interviews, observations, and documentation. Data were analyzed using interactive methods including data collection, data synthesis, data presentation, and conclusions/validation. The results of the study indicate that 1) the P5 design consists of forming a team, identifying school readiness, determining the dimensions of the Pancasila Student Profile character to be strengthened, determining the theme, planning the time, flow, assessment, and creating modules; 2) P5 management includes provocation and contextualization, P5 actions, and celebration of learning outcomes; 3) assessment processing and reporting of P5 results include collecting, processing assessment results, and compiling project report cards; 4) P5 evaluation and monitoring in the form of character strengthening and continuing good habits with the Let's Act program. Through the P5 action, the character dimensions of the Pancasila Student Profile can be strengthened in students, especially those who believe in, are devoted to God Almighty and have noble morals, work together, are independent, have global diversity, and think critically and creatively.